AUGUSTUS’S TERRITORIAL REFORM, RESPECTFUL OF ETHNICAL GROUPS - Marisa Malvasi (Bollettino della Società Geografica Italiana)
The relations between the towns of Milan and Monza have never been very hearty. At last, after long political fighting, on May 12th, 2004, the Administration of the province of Milan definitively agreed to create a new province taken from its territory, called Monza and Brianza (the second is the name of a subregion of Lombardy including Monza as its main town); and, in 2009, the new province was due to be fully operative, by the election of its new Province Council. First, it included 50 Comuni; afterwards, in 2009, other 5 were added. The parting from Milan – that had always kept Monza, only 12 km from it, but well over 100.000 inhabitants, in its shadow, – was greeted with great happiness by the inhabitants. In fact, Brianza has got its own identity, which has nothing to do with the reality of Milanese territory. Going back to the past, it was a holiday resort for the Milanese bourgeoisie, who built many villas for pleasure, endeeped in the green between the dry upper Po plain and the first morainic hills, so that Brianza received the nickname of «garden of Lombardy». Even regarding crafts and manufacturing, the industries of Brianza were very different from the ones of Milan, owing especially to treatment of timber, which became famous all over the world. Moreover, in Brianza some cultural traditions still live, reminding an agricultural past, almost unknown in other northern environs of Milan. Cancelling the Province «Monza and Brianza» is a mistake, because this denies its peculiarities and includes it newly in an agglomeration with which it has very little to share. It sounds a nonsense to cancel a province, just born, but evidently under the wrong star.